Penerapan Media Audio Visual untuk Meningkatkan Hasil Belajar IPA Pada Siswa Kelas VI SD Katolik 07 Xaverius Manado Selama Masa Pandemi Covid-19 - Mangundap, Jelvi Monica; Sobon, Kosmas (STKIP Andi Matappa Pangkep, 2021)
This study aims to describe the application of audio-visual media and to improve teacher skills, student activities and student learning outcomes. This research is a classroom action research (CAR) consisting of two cycles. The subjects in this study were sixth grade elementary school students. Data collection techniques using tests and observations. The results of the study showed that: (1) the skills of the teacher in the first cycle scored 54 or 75% with good criteria and in the second cycle the score was 61 or 84.72 with good criteria; (2) studentsâ€™ activity in the first cycle obtained a score of 258.15 or 64.54% with moderately active criteria and in the second cycle a score of 299.48% or 74.87% with active criteria; (3) studentsâ€™ learning outcomes in the first cycle of 74.19% and the second cycle of 79.97%. The suggestion in this study is that the application of Audio Visual Media can be used as a teacher reference as a solution to improve the quality of learning during pandemic of the covid-19.Â